Alleged Violation of Article 22 of Law Number 5 of 1999 Concerning the Prohibition of Monopolistic Practices and/or Unfair Business Competition (Law Number 5 of 1999) Regarding the Procurement of Rehabilitation and Renovation Packages for School Facilities and Infrastructure in Indragiri Hilir Regency 1 and 2 APBN for the 2019 Fiscal Year. Decision: 36/KPPU-I/2020 - Hodijatussolihah; Mubarak, Haikal; Fatoni, Ahmad; Muslim, Thariq; Munib; Santoso, Edi (Formosa Journal of Sustainable Research, 2024)
This study investigates a case of violation of Article 22 of Law Number 5 of 1999 related to the procurement of rehabilitation and renovation packages for school facilities and infrastructure in Indragiri Hilir Regency. Using a qualitative approach, this study analyzes the motives and factors that led to the conspiracy between PT Adhikarya Teknik Perkasa (Reported Party I), PT Kalber Reksa Abadi (Reported Party II), and the 14.1 Selection Working Group (Pokja) (Reported Party III) in the tender process. The results of the study reveal that economic factors, lack of supervision, and low penalties for violations are the main drivers of the conspiracy. In addition, the involvement of Reported Party III in designing and organizing the tender results shows weaknesses in the supervision and law enforcement system. This study provides important insights for efforts to prevent and overcome violations in government procurement of goods/services in the future